Effects of teacher- and school-level ICT training on teachers' use of digital educational resources in rural schools in China: A multilevel moderation model. (2022) - Wu, Di; Yang, Xiao; Yang, Wei; Lu, Chun; Li, Miaoyun
Highlights: ICT training factors at both of teacher- and school- level were explored. The cross-level interactions were examined by a multilevel regression analysis. Longer hours of ICT training boost teacher digital educational resources use. School ICT training plans benefit to teacher digital educational resources use. Abstract: This study aimed to explore the relationships between information and communications technology (ICT) training at teacher- and school-level and teachers' use of digital educational resources (DER) in rural schools. The sample included 826 teachers from 119 primary schools in rural areas of western China. Multilevel regression analysis revealed that rural schools should pay attention to the importance of ICT training for teachers' DER use ability. School managers could set up ICT training plans, organize more ICT training, and encourage teachers to participate in ICT training as much as possible. In addition, rural teachers should take the initiative to increase their training hours and be involved in as wide a variety of training topics as possible.